Evaluating of the Impact the Polymorphisms of IFN- γ (+874 T/A) and the Risk of HBV in Iraqi Patients - Mohamed, Najeeb Ibraheem (American Journal of Biology and Natural Sciences, 2024)
In every nation, chronic hepatitis B (HBV) is a serious health issue. A proinflammatory T-helper 1 cytokine, interferon gamma (IFN-γ) has antiproliferative and anticancer properties. Hepatitis B virus (HBV) susceptibility may be influenced by some single nucleotide polymorphisms (SNPs) in the IFN-γ and IFN-γ R1 genes. Here, we study the impact the polymorphisms of IFN-γ (+874 T/A) gene and the risk of HBV in Iraqi patients. The results showed the activities of some interleukins in serum HBV patients, where IL-1β levels indicated a significant (P <0.05) rise in patients (4.26± 0.57 pg/ml) compared to control group (1.09±0.34 pg/ml). IL-17 concentrations in serum of HBV patients indicated a significant (P <0.05) elevated in patients (48.11 ±4.72 pg/ml) compared to healthy volunteers (16.29 ±1.05 pg/ml). In the patient hepatitis infection, the T allele was 44.0%, while the allele T in the control group was 64.0%%. While the allele A in the sample of patients, which is 56.0%, compared to the allele A in control group, which was 36.0%. The frequency of these genotypes among patients was 54.7%, 18.7% and 26.6% respectively, compared with 28.0%, 24.0% and 48.0% respectively, among controls (Table 5). Statistically, there was a significant difference in the frequency of TT (OR=0.25, 95%CI=0.05-0.57, P=0.001) and AT genotype (OR= 3.43, 95%CI=9.53-0.99, p= 0.001) between patients and controls (table (5). At allelic level, the mutant allele (allele T) was more common among patients than controls (44.0% vs. 64.0%) with a highly significant difference (OR= 0.374, 95%CI=0.43-0.11, p= 0.009). Our outcomes demonstrated a significant association between HBV and genotype frequency, with patients carrying the IFN- γ +874 A/T genotype having a higher risk of hepatitis infection. Therefore, having the TT genotype is linked to a better prognosis for the HBV.